Literatura en contextos pandémicos: caras de la muerte, deseos de vida (Dossier Literatura brasileña y latinoamericana: cruce de lecturas) - Gund, Ivana Teixeira Figueiredo (2025)
This article analyzes certain implications that arise in contexts of isolation or the potential for widespread contagion. To this end, it draws upon a corpus of Latin American literary works: La Tierra en pandemia (2020) by Brazilian author Aleilton Fonseca; Mugre Rosa (2022) by Uruguayan writer Fernanda Trías; and Love in the Time of Cholera (1985) by Colombian author Gabriel García Márquez. The primary focus is to examine the political administration of human life and the strategies of collective survival depicted in these works.